BELAJAR DAN PEMBELAJARAN - Aprida Pane; Muhammad Darwis Dasopang (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2017)
This study aims to discuss the learning and intruction which is an activity conducted by teachers and students. Learning is the process of changing a behavior and knowledge. Learning process becomes one system in intruction. The intruction system consists of several components that interact with each other, that is: teachers, students, learning objectives, materials, media, methods, and evaluation. The intruction can not be done well without any interaction between the learning components, then all components of learning must cooperate  to make a efficient learning